Penelitian teori pengembangan koleksi Edward Evans di perpustakaan melalui database Google Scholar - Safitri, Arroyya Nur; Amar, Siti Chaerani Djen; Rukmana, Evi Nursanti (Jurnal Informatio, 2024)
Collection development is a critical aspect as it significantly contributes to shaping a knowledgeable, broad-minded, and morally upright younger generation, thereby enhancing the quality of education in Indonesia. The purpose of collection development is to ensure that libraries possess collections that are relevant, up-to-date, and aligned with user needs. By providing a diverse and pertinent array of books, library users can easily acquire knowledge, develop and refine their information literacy skills, cultivate their character through inspirational and moral readings, and make informed decisions in their daily lives. This study aims to offer a review based on several previous studies regarding libraries in their efforts to provide collections that meet the demands, interests, and preferences of users while considering the quality of the reading materials offered. The methodology employed is a narrative literature review, which compares and analyzes existing theories and research, referencing several prior studies related to the urgency of library collection development, with a total of five references analyzed. The stages of collection development, according to Edward Evans, include user analysis, determining selection policies, selection activities, procurement, weeding, and evaluation activities. The analysis of the five references indicates that in developing library collections, adherence to four main principles is essential: relevance, currency, completeness, and collaboration. The collection development process is a crucial activity for libraries to provide services that align with the evolving needs and interests of users over time.